2013
DOI: 10.1371/journal.pone.0065125
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen and Glucose Metabolism Are Essential for Early Embryonic Development of the Red Flour Beetle Tribolium castaneum

Abstract: Control of energy metabolism is an essential process for life. In insects, egg formation (oogenesis) and embryogenesis is dependent on stored molecules deposited by the mother or transcribed later by the zygote. In oviparous insects the egg becomes an isolated system after egg laying with all energy conversion taking place during embryogenesis. Previous studies in a few vector species showed a strong correlation of key morphogenetic events and changes in glucose metabolism. Here, we investigate glycogen and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 60 publications
4
44
0
Order By: Relevance
“…Tick embryogenesis is characterized by the formation of a cellularized blastodermal cell layer up to day 4. Thereafter, the embryo starts segment formation and initiates organogenesis 24, 54. Previously, we provided evidence that mitochondrial membrane PPX plays a role in energy metabolism in R. microplus during embryo development 18.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Tick embryogenesis is characterized by the formation of a cellularized blastodermal cell layer up to day 4. Thereafter, the embryo starts segment formation and initiates organogenesis 24, 54. Previously, we provided evidence that mitochondrial membrane PPX plays a role in energy metabolism in R. microplus during embryo development 18.…”
Section: Resultsmentioning
confidence: 93%
“…2.7.1.1; HK). This enzyme has been characterized in several organisms 19-24. Four distinct hexokinase isozymes are reported for mammalian tissues and are named types I-IV.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed a steadily growing interest in the interplay between embryonic development and metabolism. For instance, recent reports show that glucose metabolism is essential for early embryonic development in Tribolium (Fraga et al ., ) and that GSK3 controls mitochondrial function and glucose metabolism during oocyte maturation in Drosophila (Sieber et al ., ). In Rhodnius , in view of the potential for biological control of Chagas disease spread, the metabolic pathways linking blood ingestion and the development of eggs and embryos have been widely investigated (references in (Atella et al ., ).…”
Section: Embryogenesis and Metabolismmentioning
confidence: 99%
“…A simplified model of energy utilization and glycogen mobilization in the glycolytic pathway showed that glycogen storage is mobilized into the glycolytic pathway through the actions of glycogen phosphorylase (GPH) and hexokinase (HK) (Fraga et al, 2013). Its synthesis is regulated by glycogen synthase (GYS) (Bacca et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Glycogen breakdown generates glucose, which enters the glycolytic pathway and is converted to pyruvate (Fraga et al, 2013). This process leads to the generation of ATP.…”
Section: Introductionmentioning
confidence: 99%